JUSTIFICATION OF THE INFLUENCE OF PHYSIOLOGICAL PROCESSES ON THE QUALITY OF GRAIN STORAGE - Fedoriv , V.M.; Pidlisnyy , V.V.; Semenov, O.M. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The study is devoted to the analysis of the influence of physiological processes on the shelf life of high-quality grain, determination of its economic longevity and viability. The study is based on an assessment of the decrease in grain moisture and temperature, which are the main factors affecting the durability of grain during long-term storage, increasing the technological quality of grain and the viability of the seed during storage. Experimental studies were carried out during 2018-2020 at the research center "Podilya", and provided for the determination of the chemical composition and processes occurring in the grain mass, which significantly affect the storage period. Studies have shown that the technological qualities of grain during storage are influenced not only by methods and modes of drying, but also by the fractional composition, respiration rate and hydrolysis of the substance. Based on the results obtained, it can be argued that the processes of reducing the sugar content in the grain and increasing the acid number affect the quality of grain during final storage.